Functional Control of Peptide Amphiphile Assemblies via Modulation of Internal Cohesion and Surface Chemistry Switch. Issue 52 (19th August 2018) - Lu, Sheng; Cui, Weijia; Li, Jason; Sheng, Yuebiao; Chen, Pu
Abstract: Understanding the impacts of the internal cohesion and surface chemistry of supramolecular systems on the collective behaviors in the contacts between the systems and biomolecules can greatly expand the functional diversity and adaptivity of supramolecular nanostructures. Here we show how the tuned molecular interactions modulate the morphologies and internal cohesion of peptide amphiphile (PA) self‐assemblies and their resultant functions. Circular dichroism spectroscopy, fluorescence probing, atomic force and electron microscopy, along with molecular dynamics simulations, revealed that the PA self‐assembly formed compact long fibers when surface charge repulsion was screened, but formed loose short fibers or micelle‐like assemblies when hydrogen bonding was disrupted or hydrophobic core was enhanced. More importantly, depending on the strength of the phospholipid affinity for the cationic segment of the PA, the same internal cohesion of PA nanostructures can lead to either cell death or cell survival, providing unique insights into the design of supramolecular materials. Abstract : The morphology and internal cohesion of a peptide amphiphile (PA) system can be modulated by switching off electrostatic repulsion, intermolecular hydrogen bonding, or strengthening hydrophobic collapse. The modulated internal cohesion of PA self‐assemblies with switched surface chemistry can contribute drastically to different functional values as a consequence of the collective behaviors in the contacts between PA self‐assemblies and phospholipid membranes.